Propriedades estruturais e eletroquímicas de espinélios de lítio e manganês dopados para uso em baterias de lítio - Amaral, Fábio Augusto do (2005)
The spinels investigated in the present work were obtained by solid state reaction at 750 ºC for 72 h among the precursors ε-MnO2, LiOH and the respective oxides/salt of the doping ions. In order to control the particles size, all the spinels were milled in a ball milling for 30 min. The mechanical milling, associated or not to further calcination, was also used for obtaining the pure spinel LiMn2O4. The different obtained spinels were characterized by the average manganese valence (n), X ray diffractometry, electronic scanning microscopy, particles size distribution and specific superficial area. From the X ray diffractograms, spinels of single cubic phase belong to the Fd3m space group were identified. The calculated values for the unity cell parameter (a) were lower for the doped spinels (8,221 Å at 8,229 Å) than for the pure one (8,234 Å), decreasing in the following order: a(Li1,05Ga0,02Mn1,98O4) > a(Li1,05Co0,02Mn1,98O4) > a(Li1,05Al0,02Mn1,98O4) > a(Li1,05M0,02Mn1,98O3,98S0,02) > a(Li1,05M0,02Mn1,98O3,98F0,02). The values of n were higher for the doped spinels (3,56 3,50) than for the pure one (3,53 ± 0,01), decreasing in the following order: n(Li1,05Ga0,02Mn1,98O4) > n(Li1,05Co0,02Mn1,98O4) > n(Li1,05Al0,02Mn1,98O4) > n(Li1,05M0,02Mn1,98O3,98F0,02) > n(Li1,05M0,02Mn1,98O3,98S0,02). The mechanical milling after calcination changed the spinel particles in three aspects: formation of nanometer-scale particles, generation of lattice strain and partial oxidation of manganese ions. Before calcination, it allowed obtaining of pure spinel LiMn2O4 with highly disordered lattice structure, nanometer particles and high number of structural defects. A gel polymer electrolyte of the polyacrylonitrile (PAN)/polyvinylacrylate (PVA) was developed with different mixtures of organic solvents and lithium salts. From impedance measurements, the highest value of ionic conductivity (1,47 x 10-3 S cm-1) was obtained, at 25 oC, for the electrolyte prepared from the mixture (1:1) of ethyl (EC) and dimethyl (DMC) carbonates containing 1 mol L-1 of lithium tetrafluoroborate (LiBF4). Cyclic voltammetric measurements showed that this gel electrolyte only oxidizes at potentials close to 5 V vs. Li/Li+. In the charge and discharge tests, the cathodes of the doped spinels presented values of specific discharge capacity decreasing in the following order: C(Li1,05Al0,02Mn1,98S3,02O3,98) > C(Li1,05Al0,02Mn1,98F3,02O3,98) > C(Li1,05Ga0,02Mn1,98S3,02O3,98) > C(Li1,05Ga0,02Mn1,98F3,02O3,98) > C(Li1,05Co0,02Mn1,98S3,02O3,98) > C(Li1,05Co0,02Mn1,98F3,02O3,98). Although the Li1,05Al0,02Mn1,98S3,02O3,98 cathode presented the highest initial capacity value (126 mA h g-1), the Li1,05Ga0,02Mn1,98S3,02O3,98 cathode presented the lowest capacity fading (from 120 mA h g-1 to 115 mA h g-1, that is, only 4%) after three hundred cycles of charge and discharge.